Asymmetric Synthesis of Spiro[Azetidine‐3, 3′‐Indoline]‐2, 2′‐Diones via Copper(I)‐Catalyzed Kinugasa/C−C Coupling Cascade Reaction. (19th September 2022) - Zhong, Xianqiang; Huang, Meirong; Xiong, Huilan; Liang, Yuzhen; Zhou, Wei; Cai, Qian
Abstract: Spiro[azetidine‐indolines] are important scaffolds in diverse bioactive compounds. Current efforts to synthesize spiro[azetidine‐indolines] are limited to chiral spiro[azetidine‐2, 3′‐indolines]. Asymmetric synthesis of structurally similar chiral spiro[azetidine‐3, 3′‐indolines] remains unexplored. In this work, the first copper(I)‐catalyzed asymmetric Kinugasa/aryl C−C coupling cascade reaction is described. This provides a straightforward access to densely functionalized chiral spiro[azetidine‐3, 3′‐indoline]‐2, 2′‐diones in good yields and with high enantioselectivity. Abstract : Spiro[azetidine‐indolines] are important scaffolds in diversified bioactive compounds, but asymmetric synthesis of chiral spiro[azetidine‐3, 3′‐indolines] remains unexplored. In this work, a copper‐catalyzed asymmetric Kinugasa/C−C coupling cascade reaction of N ‐(2‐iodo‐aryl)‐propiolamides with nitrones has been developed, affording chiral spiro[azetidine‐3, 3′‐indoline]‐2, 2′‐diones as single diastereomers with high yields and good enantioselectivity.